Abraham Sahabat Allah - Berthold Anton Pareira (Sekolah Tinggi Widya Sasana, 2020)
Abraham is called by the three monotheistic religions as friend of God. According to Gn 18:16b-33 he by his call is to become a friend of God. What does it mean? In wisdom theology of Wis 7-8 those who seek and love wisdom are called friends of God and in Jn 15:15 Christ calls all His disciples as His friends. This study tries to explore the relationship between these texts and its significance for the life of the Church in our time.